Outsourcing of services, imported materials and the demand for heterogeneous labour : an application of a generalised box-cox function - Martin Falk; Bertrand M. Koebel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This paper examines the effects that purchased services and imported intermediate materials have on the labour demand for different skills in the manufacturing sector. We derive and estimate a factor demand system based on the generalised Box-Cox cost function nesting both the normalised quadratic and the translog functional form. We find that the impacts of output and capital growth are more important in explaining the demand for heterogeneous labour than substitution effects between labour and non-labour inputs. Similarly, the increasing use of both imported materials and purchased services is rather a consequence of output growth than input substitution.
Keywords: O33; J23; 330; Outsourcing of services; intermediate imports; heterogeneous labour; Box-Cox cost function; Verarbeitendes Gewerbe; Outsourcing; Vorprodukt; Unternehmensdienstleistung; Import; Faktorsubstitution; Arbeitsnachfrage; Humankapital; Kostenfunktion; Schätzung; Deutschland